AN ANALYSIS OF ENGLISH USED IN PROMOTING FASHION IN SOCIAL MEDIA: ANALISIS PENGGUNAAN BAHASA INGGRIS PADA PROMOSI BUSANA DI MEDIA SOSIAL - Desi Andriani; Dwi Megista Putri (LLDIKTI Wilayah X, 2021)
This research is conducted to know the use of English in promoting fashion in social media. In social media, there are many people who promoting their fashion to sell. They sometimes use English to promote in order to attract readers’ attention to buy. The aim of the research is to know how the meaning and word order of the English used in promoting fashion. This research is descriptive research. The data of the research are taken from instagram. The results of the research shows that the English used in promoting fashion is not correct and does not follow the correct word order and grammar.